2012
DOI: 10.1111/j.1440-1797.2012.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Early molecular responses of bone to obstructive nephropathy induced by unilateral ureteral obstruction in mice

Abstract: Together, it is concluded that the obstructive nephropathy has defective effects on bone, and the underlying mechanisms are the reduction of bone formation and the increase of bone resorption, which is mediated, at least partially through local angiotensin II signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…As we previously reported, the underlying mechanism may, at least partially, be due to the increased activity of the local renin-angiotensin system in bone and the pathological changes in the serum levels of minerals and parathyroid hormone in UUO mice. 5 The present results suggest that clinical bone health monitoring of the femoral greater trochanter might need to be performed for CKD patients, especially those with unilateral obstructive nephropathy.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As we previously reported, the underlying mechanism may, at least partially, be due to the increased activity of the local renin-angiotensin system in bone and the pathological changes in the serum levels of minerals and parathyroid hormone in UUO mice. 5 The present results suggest that clinical bone health monitoring of the femoral greater trochanter might need to be performed for CKD patients, especially those with unilateral obstructive nephropathy.…”
Section: Discussionmentioning
confidence: 73%
“…3 We previously reported changes in the renal expression of vitamin D metabolic enzymes and changes in calcium transporter abundance following obstructive nephropathy in mice subjected to UUO 4 and demonstrated early molecular responses of bone to unilateral obstructive nephropathy in the UUO model. 5 However, associated with the pathological alterations of vitamin D metabolism and the expression of genes involved in bone metabolism, whether trabecular bone microstructure would deteriorate in UUO mice remained to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…6) Recent in vivo studies showed that the components of RAS, such as renin, angiotensin-converting enzyme (ACE), and angiotensin II (Ang II) receptors, were expressed in the local milieu of bone, [7][8][9][10] and in vitro study identified the expression of Ang II receptors in primary osteoblasts derived from newborn mouse calvaria, 7) indicating the components of RAS are expressed locally in bone microenvironment. Our further animal studies demonstrated that the local RAS in bone was involved in age-related osteoporosis of aging mice, 11) and bone deteriorations of mice with either obstructive nephropathy 12) or type 1 diabetes.…”
mentioning
confidence: 77%
“…6) Recent in vivo studies showed that the components of RAS, such as renin, angiotensin-converting enzyme (ACE), and angiotensin II (Ang II) receptors, were expressed in the local milieu of bone, [7][8][9][10] and in vitro study identified the expression of Ang II receptors in primary osteoblasts derived from newborn mouse calvaria, 7) indicating the components of RAS are expressed locally in bone microenvironment. Our further animal studies demonstrated that the local RAS in bone was involved in age-related osteoporosis of aging mice, 11) and bone deteriorations of mice with either obstructive nephropathy 12) or type 1 diabetes.13) Other groups elucidated the involvement of skeletal RAS in the process of fracture healing in a mouse femur fracture model, 14) and the steroid-induced osteonecrosis in rabbits 10) as well as the development of postmenopausal osteoporosis in ovariectomized (OVX) animal models 15,16) and glucocorticoid-induced osteoporosis. 9) Therefore, it concludes that the local RAS exists in bone tissue and plays an important role in local bone metabolism.…”
mentioning
confidence: 80%
“…9,10) Functional studies revealed that ANG II could stimulate the differentiation and activity of osteoclasts in vivo 11) and in vitro, 12) and aggravate the loss of bone minerals in rats with osteoporosis induced by estrogen deficiency, 11) furthermore, the ANG II type 1 receptor knockout mice showed high bone mass. 13) In addition, we recently demonstrated that the local RAS in bone was involved in age-related osteoporosis of aging mice, 14) bone deteriorations of mice with either obstructive nephropathy 15) or type 1 diabetes, 16) and others elucidated the involvement of skeletal RAS in the process of fracture healing in a mouse femur fracture model. 17) Therefore, the local RAS displays important biological actions in bone tissue.…”
mentioning
confidence: 99%